The Investing Decisions during the COVID-19 Pandemic by Using the Capital Asset Pricing Model (CAPM) Method in LQ 45 Index Companies - Susanti, Elly; Ernest Grace; Nelly Ervina (Publisher Cv. Inara, 2020)
Investors need to invest wisely because the Covid 19 pandemic has gone global, so that the stock exchange has also begun to waver. Therefore, several methods are needed to determine investment decisions. This study uses the CAPM (Capital Asset Pricing Model) method and classifies and evaluates LQ 45 index companies based on the level of undervalued and overvalued. This type of quantitative descriptive research is the type of research applied in this research. In this study using saturated samples. Data processing was done using Microsoft Excel application program. The results of the study by comparing the beta value with the expected return have an inversely proportional relationship. from the 45 companies, there are 20 Undervalued companies and 25 Overvalued companies.